1999
DOI: 10.1177/1077559599004002003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Maltreatment of Children of Battered Women: Methodological and Ethical Considerations

Abstract: This article reviews considerations to be made when assessing maltreatment in children of battered women and offers guidelines to improve research and practice in the field. Methodological problems regarding the measurement of child maltreatment experiences are discussed. Next, techniques appropriate for assessing maltreatment of children of battered women are reviewed, including parent questionnaires and interviews, children's reports, case record reviews, and observations. In addition, ethical concerns are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…It has been suggested that such exposure can be particularly traumatic for children aged 5 years and less because of a reduced repertoire of coping mechanisms and the increased vulnerability of this age group in terms of physical and emotional development (e.g. Kerig & Fedorowicz 1999). Instances whereby adults hold excessive power over children and fail to take children's rights into consideration in a meaningful way are widespread in our society and this has to be regarded as constituting emotional abuse.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that such exposure can be particularly traumatic for children aged 5 years and less because of a reduced repertoire of coping mechanisms and the increased vulnerability of this age group in terms of physical and emotional development (e.g. Kerig & Fedorowicz 1999). Instances whereby adults hold excessive power over children and fail to take children's rights into consideration in a meaningful way are widespread in our society and this has to be regarded as constituting emotional abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Although the summary measure of maltreatment utilized in the initial phase of our study was not significantly related to C/U traits (see Table 2), we extended our examination by also considering the correlation of C/U traits to the five subtypes of maltreatment assessed by the maltreatment experiences scale (ME; Kerig and Fedorowicz 1999): (1) physical abuse, (2) sexual abuse, (3) psychological abuse, (4) neglect, and (5) exposure to interparental violence. Results in all cases were insignificant (physical r = -.05; sexual r = .00; psychological r = -.01; neglect r = -.01; exposure r = -.03).…”
Section: Exploratory Post Hoc Analysesmentioning
confidence: 99%
“…Hospital social workers completed the maltreatment experiences scale (ME; Kerig and Fedorowicz 1999), a measure that provides an overall maltreatment score as well as scale scores for physical, sexual, and psychological abuse, neglect, and exposure to interparental violence. Ratings were made based on social workers' examinations of children's case records, interviews with the children and their parents, and interviews with mental health professionals who had been involved with the child in the community.…”
Section: Child Maltreatmentmentioning
confidence: 99%
“…2002). Therefore, the position of child advocacy groups is that children's welfare needs must be examined outside of the preconceived notion that portrays abused women as well‐functioning mothers just because they are victims (Kerig & Fedorowicz 1999).…”
Section: Two Contrasting Views On Abused Women's Motheringmentioning
confidence: 99%